Alternative fleet configuration for Malmberget mine - Skawina, Bartlomiej; Salama, Abubakary; Greberg, Jenny; Sundqvist, Fredrik (Luleå tekniska universitet, Geoteknologi, 2015)
This report is part of the work done by Luleå University of Technology within the EU 7th framework project I2Mine, Innovative Technologies and Concepts for the Sustainable and Intelligent Deep Mine of the Future. The work is performed within work package 2 Novel mining and underground processing methods, subtask 2.1.1 Novel mining methods and processes for deep, steeply dipping orebodies. För godkännande; 2015; 20150526 (barska) I2Mine, Innovative Technologies and Concepts for the Intelligent Deep Mine of the Future